A STUDY ON AWARENESS, ATTITUDE AND BUYING BEHAVIOUR OF GEN Z (International Journal of Food and Nutritional Sciences, 2022)
The United Nations established Sustainable Development Goals (SDGs) in the year 2015 aiming to motivate developed and developing nations to share blueprint for peace and prosperity for people and the planet, now and into the future. The 12th Sustainable development goal is “responsible consumption and production”. The consumption decisions made everyday by individuals has to be guided by sustainable means and knowledge of sustainable options. One of the simplest ways of being an environmentally conscious individual Is to make sustainable buying decisions which is influence by the awareness, the intention of making a change, product knowledge, willingness to spend on sustainable options which all form the attitude of an individual. The present study aims to study the interrelationships of all the said variables using primary data which will be analyses using chi square test. The study focuses on the upcoming generation of individuals who are getting newer purchasing power and unlike the millennials – who came of age during the Great Recession – this new generation was in line to inherit a strong economy with record-low unemployment. The perception, attitude and buying behaviour of Gen Z hence becomes very significant to determine the overall consumption of sustainable products in the years to come.The idea of sustainability has been gaining importance and momentum in the recent years with the shifts in the perception and exposure generations after generations. The generation of the times is Gen Z which is expected to change the overall consumer attitude and behaviour to a great extent especially in the context of sustainability. The present study aims to understand the perception, attitude and buying behaviour of Gen Z with respect to sustainable options.